O SER E ESTAR DA AÇÃO DOCENTE: UMA REFLEXÃO NECESSÁRIA - Mikelli Cristina Pacito Benites; Rosângela Regina Marcicano Capelasso; Carmen Lúcia Dias (Universidade do Oeste Paulista, 2011)
The purpose of the present study is to present reflections of different authors about being and staying as a teacher in relation to the teaching practice facing the social and political function associated to the profession. These reflections about changes and innovations in the teaching-learning process aim to contribute to the education of critical citizens for the achievement of needed social transformations. To reflect about the teaching practice is a significant task for changing the school reality in which we are inserted.